A Case Study of Moral Disengagement on the Juvenile Sex Offenders - Dessi Christanti; Suryanto -; Muhammad Ghazali Bagus Ani Putra (Journal of Educational, Health and Community Psychology, 2019)
Abstract This study aims to explore the moral disengagement in juvenile sex offenders and how their social environment relates to moral disengagement. Cognitive processes have a role in encouraging adolescents to fornicate a girl. The theory of moral disengagement can explain why adolescents do sexual offenses. This research used a qualitative method of a case study. The number of participants was seven adolescents aged 16-18 years and had been found guilty of forcibly by the court. The interview method was used to collect the data. The results showed that the juvenile sex offenders used seven forms of moral disengagement of Bandura’s theory: moral justification, euphemistic labeling, displacement of responsibility, diffusion of responsibility, distortion of consequences, dehumanization, and attribution of blame. The result also showed that juvenile sex offenders used active avoidance to minimize their guilty feeling. This was a different form of early moral disengagement form of Bandura. The social environments identified in this research were the family condition, permissive environmental, peer group, pornographic exposure, lack of appreciation of religion, and the absence of adverse reaction from the victim. Keywords: moral disengagement, The juvenile sex offenders, social environment, case study